Britain and Germany between the wars - Gilbert, Martin (London, 1964)
This series is designed to study problems in preference to periods. Each volume will contain sections dealing with historiography, documents, and a consideration of the wider issues, although the balance between the three will vary in each case. This approach encourages the student to deal in his own way with the problems raised by historical docu ments and the historiography of the issues in question and he is made aware of the wider perspectives of history.
Keywords: War - Great Britain - Germany